Dresses and ties: the effect of grammatical gender and stereotypical semantic bias in three Spanish-speaking communities - Gabriela Mariel Zunino; Miriam Aguilar; Noelia Ayelén Stetie; Camila Martínez Rebolledo; José Antonio Hinojosa (Language and Cognition)
Stereotype construction is a complex process, with multiple relations to language processing, that combines collective sociocultural factors with individual cognitive elements. Regarding gendered languages, there is a debate about the effect of grammatical gender on the representation of inanimate entities. To evaluate the potential interaction between gender stereotypes and gender morphology on words that refer to inanimate entities in three different communities of Spanish speakers, we developed a task of conscious judgments on the level of association to men or women of words that refer to objects. In a 3 × 2 × 3 × 2 design, we manipulated Semantic Bias (gender stereotypicality), with three levels (male, e.g., martillo, hammer-M; female, e.g., vestido, dress-M; neutral, e.g., lápiz, pencil-M); Morphology, with two levels (masculine, e.g., vestido, dress-M; feminine, e.g., pulsera, bracelet-F); Linguistic variety, with three levels (Argentine, Chilean and Peninsular) and Questionnaire, with two levels (related to men vs. related to women). The results showed that grammatical gender has an effect on words that refer to inanimate entities when those words do not carry a strong stereotypical association (neutral items), semantic bias related to gender stereotypes overshadows any potential effect of grammatical gender in biased items, and there are differences depending on the community (Argentine, Chilean and Peninsular).